2022
DOI: 10.3390/ma15062301
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Seismic Behavior of PC Walls with Alveolar-Type Horizontal Joint under Pseudo-Static Loading

Abstract: There are many horizontal joints on precast concrete (PC) wall panel structures, which certainly has a significant impact on the seismic behavior of structures. This paper proposes a novel alveolar-type horizontal joint, which has advantages of convenient and rapid assembly. Six precast concrete wall specimens with alveolar-type joints were designed and constructed, and they were weakly connected by spliced rebars anchored into grouted sleeves to meet the requirements of structural performance. The pseudo-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The axial compression ratio was 0.1 and the joint mortar was a high-strength material with a nominal strength of 50 Mpa. Conversely, the length of CW5~CW7 was 600 mm, with a 50 mm alveolar-type depth, and the axial compression ratio was controlled as 0, 0.1, and 0.2 [2], respectively. The cement mortar was used as a normal material, for which the design strength was 30 Mpa.…”
Section: Experimental Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The axial compression ratio was 0.1 and the joint mortar was a high-strength material with a nominal strength of 50 Mpa. Conversely, the length of CW5~CW7 was 600 mm, with a 50 mm alveolar-type depth, and the axial compression ratio was controlled as 0, 0.1, and 0.2 [2], respectively. The cement mortar was used as a normal material, for which the design strength was 30 Mpa.…”
Section: Experimental Preparationmentioning
confidence: 99%
“…In recent years, precast construction technology has increased progressively and has been employed in a variety of structural applications. Prefabricated concrete wall panel building has become one of the most important developments in housing construction because of its sustainable development advantages, such as how it reduces formwork demand, saves on labor costs, and its quality control [1,2]. Prefabricated concrete wall panel building is a precast concrete construction technology that adopts factory precast concrete wall panel members as the main bearing members, which are connected into an integral whole through the on-site assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the innovative precast RC shear walls are reliable, and no rebar is pulled out or seriously slipped. Cheng et al 20 conducted pseudo‐static loading tests of precast RC shear walls with alveolar‐type joints. It was concluded that the shear capacity and energy dissipation capacity of precast RC shear wall dramatically enhanced by adding alveolar‐type joints.…”
Section: Introductionmentioning
confidence: 99%
“…Poor shear performance at the horizontal joints can directly impact the overall reliability of these prefabricated concrete structures [20]. Currently, horizontal joint connection methods for prefabricated concrete wall panel structures include grouted sleeve connections, mortar anchorage overlaps, and bolt connections [21][22][23]. Research has shown that the interface connections between the horizontal joint layer and both the top and bottom prefabricated concrete components should not be overlooked [24,25].…”
Section: Introductionmentioning
confidence: 99%